Impact of high‐sensitivity cardiac troponin T on survival and rehospitalization after transcatheter aortic valve replacement. Issue 6 (2nd June 2021) - Schoechlin, Simon; Schulz, Undine; Ruile, Philip; Hein, Manuel; Eichenlaub, Martin; Jander, Nikolaus; Neumann, Franz‐Josef; Valina, Christian
Abstract: Background: Constant elevations of the serum concentration of cardiac troponin T (TnT) indicate a myocardial injury that may affect the long‐term outcome of transcatheter aortic valve replacement (TAVR). Objectives: We sought to investigate the impact of pre‐TAVR TnT on outcomes after TAVR during long‐term follow‐up. Methods: In a retrospective, observational study we compared long term outcomes after TAVR between tertiles of preinterventional high‐sensitivity TnT. Systematic follow‐up was performed annually for 5 years. The primary endpoint was a composite of all‐cause death and any rehospitalization. Results: Between 2010 and 2018, 2, 129 patients with severe aortic valve stenosis underwent TAVR at our institution (mean age 82.6 years, 57.2% female, logistic EuroSCORE 20.5 ± 15.8). Boundaries for TnT tertiles were <21 ng/L and >42 ng/L. The median follow‐up was 895 days. Three‐year incidences for the primary endpoint were 70.9%, 76.6%, and 81.7% in the low, middle, and high tertile (log rank p  < .001). Compared with the first tertile, the corresponding adjusted hazard ratios were 1.23 (95%‐CI 1.08–1.40, p  < .001) and 1.50 (95%‐CI 1.32–1.70, p  < .001) for the second and third tertile. We found consistent differences between TnT strata for all‐cause death (3‐year incidences 23.3%, 33.3%, and 47.1%; adjusted p  < .001) and rehospitalization (3‐year incidences 64.7%, 68.7% and 72.0%; adjusted p  < .001), including significant differences in deaths ( p  < .001). The association between TnT and outcome was independent of coronary artery disease or low aortic valve gradient. Conclusions: TnT before TAVR is strongly associated with all‐cause death and rehospitalization during 3‐year follow‐up.